Exercise training attenuates skeletal muscle fat infiltration and improves insulin pathway of patients with immune-mediated necrotizing myopathies and dermatomyositis - Diego Sales de Oliveira,; Isabela Bruna Pires Borges,; Suely Kazue Nagahashi Marie,; Antonio Marcondes Lerario,; Sueli Mieko Oba-Shinjo,; Samuel Katsuyuki Shinjo, (Archives of Rheumatology, 2023)
Objectives: This study aims to evaluate the effects of exercise training on intramuscular lipid content and genes related to insulin pathway in patients with systemic autoimmune myopathies (SAMs). Patients and methods: Between January 2016 and May 2019, a total of seven patients with dermatomyositis (DM; 3 males, 4 females; mean age: 49.8±2.3 years; range, 43 to 54 years), six with immune mediated necrotizing myopathy (IMNM; 3 males, 3 females; mean age: 58.5±10.6 years; range, 46 to 74 years), and 10 control individuals (CTRL group; 4 males, 6 females; mean age: 48.7±3.9 years; range, 41 to 56 years) were included. The muscle biopsy before and after the intervention was performed to evaluate the intramuscular lipid content. Patients underwent a combined exercise training program for 12 weeks. Skeletal muscle gene expression was analyzed and the DM versus CTRL group, DM pre- and post-, and IMNM pre- and post-intervention were compared. Results: The DM group had a higher intramuscular lipid content in type II muscle fibers compared to the CTRL group. After the intervention, there was a reduction of lipid content in type I and II fibers in DM and IMNM group. The CTRL group showed a significantly higher expression of genes related to insulin and lipid oxidation pathways (AMPKβ2, AS160, INSR, PGC1-α, PI3K, and RAB14) compared to the DM group. After exercise training, there was an increase gene expression related to insulin pathway and lipid oxidation in DM group (AMPKβ2, AS160, INSR, PGC1-α, PI3K, and RAB14) and in IMNM group (AKT2, AMPKβ2, RAB10, RAB14, and PGC1-α). Conclusion: Exercise training attenuated the amount of fat in type I and II muscle fibers in patients with DM and IMNM and increased gene expression related to insulin pathways and lipid oxidation in DM and IMNM. These results suggest that exercise training can improve the quality and metabolic functions of skeletal muscle in these diseases.